2020
DOI: 10.1186/s12891-020-3114-y
|View full text |Cite
|
Sign up to set email alerts
|

Bone transport versus acute shortening for the management of infected tibial bone defects: a meta-analysis

Abstract: Background: The treatment for infected tibial bone defects can be a great challenge for the orthopaedic surgeon. This meta-analysis was conducted to compare the safety and efficacy between bone transport (BT) and the acute shortening technique (AST) in the treatment of infected tibial bone defects. Methods: A literature survey was conducted by searching the PubMed, Web of Science, Cochrane Library, and Embase databases together with the China National Knowledge Infrastructure (CNKI) and the Wanfang database fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…It’s generally recognized that the defect and deformity can be resolved simultaneously by the bone transport using an external fixator, allowing the patient to utilize the limb function earlier to prevent joint stiffness or arthritis [ 1 4 , 17 ], However, this technique is also a great challenge for surgeons since the long EFT and tricky complications [ 18 , 19 ]. Some interventions have been applied to shorten the EFT, such as fixation combined with an internal and external fixator, cyclic distraction and compression technique at the consolidation stage, or injection of biological agents that promote bone healing in the distraction area, etc.…”
Section: Discussionmentioning
confidence: 99%
“…It’s generally recognized that the defect and deformity can be resolved simultaneously by the bone transport using an external fixator, allowing the patient to utilize the limb function earlier to prevent joint stiffness or arthritis [ 1 4 , 17 ], However, this technique is also a great challenge for surgeons since the long EFT and tricky complications [ 18 , 19 ]. Some interventions have been applied to shorten the EFT, such as fixation combined with an internal and external fixator, cyclic distraction and compression technique at the consolidation stage, or injection of biological agents that promote bone healing in the distraction area, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The Ilizarov technique has been successfully used for many years to treat bone defects caused by pathological diseases [ 4 , 6 8 , 16 – 18 ]. Bone transport using a unilateral external fixator, based on the Ilizarov technique, has been widely utilized for the treatment of CSBD caused by infection in lower limbs [ 2 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonunion caused by infection is a common complication after the treatment of the lower extremity open fracture, which needs plenty of medical resources to resolve [ 1 6 ]. Particularly, the bone defect caused by infection is one of the challenging musculoskeletal problems in orthopaedic surgery [ 4 , 7 , 8 ]. Based on the Ilizarov technique, bone transport using a unilateral external fixator is a practical method for the management of bone defects in lower limbs.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that the “shortening–lengthening technique” shortens the bone healing time and decreases the proportion of bone grafting. 6 , 15 , 16 , 29 …”
Section: Discussionmentioning
confidence: 99%